On the future of the giant South American river turtle Podocnemis expansa - Forero-Medina, Germán; Ferrara, Camila Rudge; Vogt, Richard Carl; Fagundes, Camila Kurzmann; Balestra, Rafael Antônio M.; Andrade, Paulo César Machado; Lacava, Roberto Victor; Bernhard, Rafael; Lipman, Alison J.; Lenz, Ana Júlia; Ferrer, Arnaldo; Calle, Arsenio; et al. (Oryx, 2019)
There is a long history of exploitation of the South American river turtle Podocnemis expansa. Conservation efforts for this species started in the 1960s but best practices were not established, and population trends and the number of nesting females protected remained unknown. In 2014 we formed a working group to discuss conservation strategies and to compile population data across the species' range. We analysed the spatial pattern of its abundance in relation to human and natural factors using multiple regression analyses. We found that > 85 conservation programmes are protecting 147,000 nesting females, primarily in Brazil. The top six sites harbour > 100,000 females and should be prioritized for conservation action. Abundance declines with latitude and we found no evidence of human pressure on current turtle abundance patterns. It is presently not possible to estimate the global population trend because the species is not monitored continuously across the Amazon basin. The number of females is increasing at some localities and decreasing at others. However, the current size of the protected population is well below the historical population size estimated from past levels of human consumption, which demonstrates the need for concerted global conservation action. The data and management recommendations compiled here provide the basis for a regional monitoring programme among South American countries. © Fauna & Flora International 2019.